Natalizumab-immunogenicity evaluation in patients with infusion related events or disease exacerbations - Ciano-Petersen, Nicolás Lundahl; Aliaga-Gaspar, Pablo; Hurtado-Guerrero, Isaac; Reyes, Virginia; Rodriguez-Bada, José Luis; Rodriguez-Traver, Eva; Brichette-Mieg, Isabel; Leyva Fernández, Laura; Serrano-Castro, Pedro; Alonso, Ana; Oliver-Martos, Begoña (Frontiers in Immunology, 2023)
Introduction Natalizumab is a biologic drug for relapsing-remitting multiple sclerosis that may induce the generation of anti-drug antibodies in some patients. Anti-natalizumab antibodies (ANA) increase the risk of adverse events and reduce efficacy, being useful biomarkers for monitoring treatment response. Methods Retrospective observational study including MS patients treated with natalizumab that experienced infusion-related events (IRE) or disease exacerbations (DE). ANA were tested by Elisa including a screening and a confirmation assay. Patients were further classified as transient (one positive result) or persistent (two or more positive results) ANA. Results A total of 1251 MS patients were included and 153 (12.3%) had ANA with at least one single point determination, which were more frequent among patients with IRE compared to those with DE (21,6% vs.10.8%) during the first six infusions. Two or more determinations ANA were performed in 184 patients, being 31.5% permanently positive and 7.1% transiently positive. Interestingly, 26.1% of patients that experienced DE had persistent ANA, while 2.6% were transient. In contrast, 43% of patients with IRE had persistent ANA, and 9.3% had transient antibodies. Patients with persistent antibodies had more frequently high levels at the first sampling compared to patients with transient ANA. Conclusion Real-world evidence shows that the presence of ANA is behind an important percentage of patients treated with natalizumab that experience IRE, as well as DE but in a lower degree. These findings support the need to systematically evaluate ANA towards a personalized management of these patients to avoid undesired complications.